Community-Based Tourism as a Driver of Rural Transformation: A Qualitative Study of Cibeber Village, Purwakarta, West Java Province, Indonesia - Candra Hidayat; Yi Zeng; Michael Khrisna Aditya; Haryo Wicaksono; Ervina Taviprawati (Institut Pariwisata Trisakti, 2026)
The development of emerging tourist villages has become a crucial strategy for promoting local economic growth through a Community-Based Tourism (CBT) approach. This study aims to analyze the transformation process of Cibeber Village into an emerging tourist village, identify supporting and inhibiting factors, evaluate the role of the community and local institutions, and formulate sustainable development strategies. The research employed a qualitative approach, with data collected through in-depth interviews, field observations, and documentation. The findings indicate that the village transformation occurs gradually, influenced by natural and cultural potential, active community participation, and the role of institutions such as village-owned enterprises (BUMDes) and tourism awareness groups (Pokdarwis). Supporting factors include community initiatives, village government support, and unique tourism potential, whereas major obstacles involve community capacity limitations, infrastructure, and coordination among stakeholders. Recommended development strategies include enhancing community capacity, strengthening institutions, developing infrastructure, digital promotion, and preserving local wisdom. This study provides a theoretical contribution in the form of an integrative CBT framework at the emerging stage and offers practical implications for village managers, policymakers, and tourism practitioners in developing sustainable tourist villages. Keywords: emerging tourist village, community-based tourism (CBT), community participation, village institutions, sustainable development